Perancangan Bark Belt Convey0r 27B Kapasitas 244 Ton/Jam - Arief Yanuar Chrise; Syafri Syafri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
In this research is described the bark conveyor calculations that must be performed in accordancewhit theories exist in the literature and the real situation. This is done to avoid failure during the ongoing production process. Bark conveyor has a length of 85 meters, a slope angle of 16 °, speed of 1.3 m/s and a payload capacity of 244 tons/hour. The analysis includes analysis of bark belt conveyor, idler rollers, pulleys, power motor, and a belt take-up. From thecalculations were resulted the weight belt at 11,286 kg/m,an idler rollers outside diameter of 108 mm,drive pulley diameter of 500 mm, tail pulley diameter of 400 mm, the motor power of 62,32 kW and length of belt take up by 0,85 m. This was influenced by the parameters in the calculation.Keyword : bark conveyor, belt, roller idler, drive motor.